2018
DOI: 10.1038/s41388-018-0391-0
|View full text |Cite|
|
Sign up to set email alerts
|

Primary tumor-derived exosomes facilitate metastasis by regulating adhesion of circulating tumor cells via SMAD3 in liver cancer

Abstract: Hepatocellular carcinoma (HCC) is a fatal disease and patients with HCC frequently die from metastasis. The mechanisms of HCC metastasis are not completely understood. In the present study, in vitro and in vivo data showed that HCC cells promoted cancer cell proliferation and lung metastases formation in a paracrinal/endocrinal way. We found that HCC-derived exosomes mediated this phenomenon and observed enhanced cell adhesion in the presence of these malignant exosomes. We further identified that reactive oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(100 citation statements)
references
References 33 publications
2
96
0
Order By: Relevance
“…This involvement of Rab27A in pro-metastatic changes was confirmed when knock-down of Rab27A in melanoma mice models resulted in decreased metastasis formation in vivo [64]. In hepatocellular carcinoma, the uptake of exosomes from adherent hepatocellular carcinoma cells by detached cancer cells resulted in the release of adhesion-associated proteins and mRNA that induced the attachment of these cells, which was in turn associated with lung metastasis in vivo [65]. In ovarian cancer, injection of exosomes from highly metastatic cell lines in mice models resulted in increased ability to metastasise when compared with exosomes from low-metastatic-capacity cells [66].…”
Section: Induction Of Pro-metastatic Phenotypesmentioning
confidence: 77%
“…This involvement of Rab27A in pro-metastatic changes was confirmed when knock-down of Rab27A in melanoma mice models resulted in decreased metastasis formation in vivo [64]. In hepatocellular carcinoma, the uptake of exosomes from adherent hepatocellular carcinoma cells by detached cancer cells resulted in the release of adhesion-associated proteins and mRNA that induced the attachment of these cells, which was in turn associated with lung metastasis in vivo [65]. In ovarian cancer, injection of exosomes from highly metastatic cell lines in mice models resulted in increased ability to metastasise when compared with exosomes from low-metastatic-capacity cells [66].…”
Section: Induction Of Pro-metastatic Phenotypesmentioning
confidence: 77%
“…Some groups revealed that HCC promoted metastasis by secreting exosomes via the SMAD3 or the mitogen-activated protein kinase signaling pathway. 35,36 Exosomal miR-93 or miR-210 were found to influence migration, invasion, and angiogenesis of HCC. 37,38 In combination with our data, miR-296 exosome was released by HCC cells to act on HDLEC cells and then modulated lymphangiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, gastric cancer (GC)-derived exosomes promote tumor cell proliferation by activating phosphatidylinositol 3-kinase (PI3K)/Akt and mitogen-activated protein kinase (MAPK) / extracellular signal-regulated kinase (ERK) pathways (33). (HCC)-derived exosomes of primary hepatocellular carcinoma regulate the adhesion of HCC cells in circulation by transmitting SMAD family member 3 (SMAD3), thus promoting tumor metastasis (34). Exoskeletons derived from (HNSCC) in head and neck squamous cell carcinoma can promote angiogenesis by reprogramming receptor endothelial cells (34).…”
Section: Discussionmentioning
confidence: 99%
“…(HCC)-derived exosomes of primary hepatocellular carcinoma regulate the adhesion of HCC cells in circulation by transmitting SMAD family member 3 (SMAD3), thus promoting tumor metastasis (34). Exoskeletons derived from (HNSCC) in head and neck squamous cell carcinoma can promote angiogenesis by reprogramming receptor endothelial cells (34). In addition, exosomes were found in various body uids such as saliva, blood and urine (35,36).…”
Section: Discussionmentioning
confidence: 99%